Characterisation of canine CD34+/CD45 diminished cells by colony-forming unit assay and transcriptome analysis - Ayabe, Taro; Hisasue, Masaharu; Yamada, Yoko; Nitta, Suguru; Kikuchi, Kaoruko; Neo, Sakurako; Matsumoto, Yuki; Horie, Ryo; Kawamoto, Kosuke (Frontiers in Veterinary Science, 2022)
Hematopoietic stem and progenitor cells (HSPCs) are used for transplantation to reconstruct the hematopoietic pathways in humans receiving severe chemotherapy. However, the characteristics of canine HSPCs, such as specific surface antigens and gene expression profiles, are still unclear. This study aimed to character the hematopoietic ability and gene expression profiles of canine bone marrow HSPCs in healthy dogs. In this study, the CD34 positive (CD34+) cells were defined as classical HSPCs, CD34+/CD45 diminished (CD45dim) cells as more enriched HSPCs, and whole viable cells as controls. Hematopoietic abilities and gene expression profiles were evaluated using colony-forming unit assay and RNA-sequencing analysis. Canine CD34+/CD45dim cells exhibited a significantly higher hematopoietic colony formation ability and expressed more similarity in the gene expression profiles to human and mouse HSPCs than that of the other cell fractions. Furthermore, the canine CD34+/CD45dim cells expressed candidate cell surface antigens necessary to define the canine hematopoietic hierarchy roadmap. These results indicate that the canine CD34+/CD45dim cells express the HSPC characteristics more than the other cell fractions, thereby suggesting that these cells have the potential to be used for studying hematopoietic stem cells in dogs.